O estar-junto na vida cotidiana no Parque Alvorada - Jorge Backes: táticas e astúcias - Motta Filho, Manoel do Carmo da (2015)
In quotidian life we can identify the bubbling of interactions from guys in spaces they frequent. The way they act, take on roles and develop their activities is influenced by the context on which they take part in and in which compose daily practices that constitute the ordinary life of them. It should be remembered this situation is not always consciously remembered by them, because this includes a line of anodyne events that integrate the lived and experienced in the spaces. From this point of view we constituted the investigation for master s thesis: The being-together in quotidian life in Parque Alvorada Jorge Backes: tactics and gimmicks . For supporting the investigation we elaborated the following questions of research: Which quotidian inventions of the guys with and in the space of the Park? Which the ethic of esthetics present in the manners of doing of the guys in relation to the rules of utilization of the Park and those that characterize one link to another? Which the educational principle of tactics, gimmicks, quotidian inventions and interactions between in quotidian of the guys? The research had as its aim: recognize the pratices of utilization of the Park in the guys s quotidian, with attention to the elements that characterize a lower educational process in established interactions by guys on that place. Supported in ethnographic assumptions, we performed the incursions in field, guided by observation and notes in a writing pad and a field diary, with photographic register, together with the research for documents that helped us in the understanding of locus of research. In material analysis we established effort to gather practices and quotidian experiences with the work done by the painter Georges Seurat in respect of the habits of utilization by the users from Great Island of Jatte on XIX century in Paris, together with authors who offer technical and methodological support of investigation, such as, Michel de Certeau (1994); Michel Maffesoli (1998; 2001; 2004; 2005; 2007; 2009; 2010); Marc Augé (2012),Georges Balandier and Silvio Gallo (2002). In this way, in research, we showed the characteristics of the utilization practices of the guys which reinvented the spaces, turned them in qualified and significant places: interact in the construction of elements they share and (re)link them to a group which they build their subjectivity, at the same time they subjective other through a smaller education process, which the guys operate deterritorialization from prescription of spaces and plates that ends by establishing new ways of doing and expands the repertory of tactics and gimmicks to be added in new connections.